Molecular and cellular mechanisms of inflammation in atherosclerosis - Popa-Fotea, Nicoleta-Monica; Ferdoschi, Corina-Elena; Micheu, Miruna-Mihaela (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis and its complications are a major cause of morbidity and mortality worldwide in spite of the improved medical and invasive treatment in terms of revascularization. Atherosclerosis is a dynamic, multi-step process in which inflammation is a ubiquitous component participating in the initiation, development, and entanglements of the atherosclerotic plaque. After activation, the immune system, either native or acquired, is part of the atherosclerotic dynamics enhancing the pro-atherogenic function of immune or non-immune cells, such as endothelial cells, smooth muscle cells, or platelets, through mediators such as cytokines or directly by cell-to-cell interaction. Cytokines are molecules secreted by the activated cells mentioned above that mediate the inflammatory component of atherosclerosis whose function is to stimulate the immune cells and the production of further cytokines. This review provides insights of the cell axis activation and specific mechanisms and pathways through which inflammation actuates atherosclerosis.